2009
DOI: 10.1002/jcc.21328
|View full text |Cite
|
Sign up to set email alerts
|

Trends of the bonding effect on the performance of DFT methods in electric properties calculations: A pattern recognition and metric space approach on some XY2 (X = O, S and Y = H, O, F, S, Cl) molecules

Abstract: A test set of 10 molecules (open and ring forms of ozone and sulfur dioxide as well as water and hydrogen sulfide and their respective fluoro- and chloro-substituted analogs) of specific atmospheric interest has been formed as to assess the performance of various density functional theory methods in (hyper)polarizability calculations against well-established ab initio methods. The choice of these molecules was further based on (i) the profound change in the physics between isomeric systems, e.g., open (C(2v)) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 104 publications
1
11
0
Order By: Relevance
“…Pattern recognition has long found application in Chemistry [93]. Our use of such techniques extends the application of pattern recognition (PR) to a hitherto unreached field: computational quantum chemistry (CQC The above-mentioned methodology has found application in various quantum chemistry problems [94][95][96]. We give here only a few essential points and definitions.…”
Section: Proximity Similarity and Order In Spaces Of Theoretical Dementioning
confidence: 98%
“…Pattern recognition has long found application in Chemistry [93]. Our use of such techniques extends the application of pattern recognition (PR) to a hitherto unreached field: computational quantum chemistry (CQC The above-mentioned methodology has found application in various quantum chemistry problems [94][95][96]. We give here only a few essential points and definitions.…”
Section: Proximity Similarity and Order In Spaces Of Theoretical Dementioning
confidence: 98%
“…[24][25][26] However, to our knowledge, there are no theoretical results at this level for frequency-dependent hyper(polarizabilities). [24][25][26] However, to our knowledge, there are no theoretical results at this level for frequency-dependent hyper(polarizabilities).…”
Section: Introductionmentioning
confidence: 95%
“…[9][10][11][12][13][14] Despite the small number of electrons, ozone is not a simple molecule to treat theoretically. [24][25][26] Results of density functional theory, many-body perturbation theory, and coupled cluster calculations based on the finite-field scheme, with especially constructed basis sets, have been reported for the static (hyper)polarizabilities a) Permanent address: Coordenação de Física, Departamento II, Instituto Federal de Goiás, Goiânia, Goiás 74055-110, Brazil. [15][16][17] Coupled cluster, configuration interaction, and multiconfigurational calculations revealed that the inclusion of the connected triple and even quadruple excitations is essential to yield results in good agreement with experiments for the equilibrium geometry, vibrational frequencies, and dissociation energy.…”
Section: Introductionmentioning
confidence: 99%
“…As little relevant information exists in the literature, we focus carefully on the performance of the theoretical methods. To this end, we employ a graph-theoretic method based on generalized metrics [20] which has been successfully applied to a variety of molecular property studies [21][22][23][24].…”
Section: Introduction and Basic Theoretical Considerationsmentioning
confidence: 99%